2001
DOI: 10.1080/09500340150203620
|View full text |Cite
|
Sign up to set email alerts
|

Theory for double beam interference microscopes with coherence effects and verification using the Linnik microscope

Abstract: A theoretical model for the interferogram from double beam interference microscopes, which takes into account the coherence eVects, is presented. The model is based on the general imaging theory of a lens in defocus. For the case of zero relative lateral displacements between the reference and object beams a simpli ed expression is found for the defocus and path length dependence of the interferogram. Based on this expression the characteristics of the interferogram are studied and special attention is devoted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 15 publications
1
20
0
3
Order By: Relevance
“…The distinction between the two techniques is somehow misleading as many researchers now refer to any doublebeam OCM as an OCT system. Coherence effects and interplay between spatial and temporal coherence are subjects of interest [36,[43][44][45] because they help to understand the physics behind the behavior of low-coherence interference microscopy (LCIM) systems. In recent studies [36,45] the present author concentrated on the distinction between the spatial versus temporal coherence effects showing that in fact each plays a different role in an OCT system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The distinction between the two techniques is somehow misleading as many researchers now refer to any doublebeam OCM as an OCT system. Coherence effects and interplay between spatial and temporal coherence are subjects of interest [36,[43][44][45] because they help to understand the physics behind the behavior of low-coherence interference microscopy (LCIM) systems. In recent studies [36,45] the present author concentrated on the distinction between the spatial versus temporal coherence effects showing that in fact each plays a different role in an OCT system.…”
Section: Introductionmentioning
confidence: 99%
“…Coherence effects and interplay between spatial and temporal coherence are subjects of interest [36,[43][44][45] because they help to understand the physics behind the behavior of low-coherence interference microscopy (LCIM) systems. In recent studies [36,45] the present author concentrated on the distinction between the spatial versus temporal coherence effects showing that in fact each plays a different role in an OCT system. It was shown that the coherence region is determined by the temporal coherence only when the path-length difference is scanned in a region where the reference and sample beams are perfectly longitudinally spatially coherent (collimated).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bandwidth of the light source and the numerical aperture (NA) of the objective lens mainly determines the coherence length. [19][20][21] Although a white light source such as a halogen light creates a shorter coherence length than those from LEDs making detection of the interference fringes on test surfaces less easy, a halogen light is used in this method. This is because this methodology involves a numerical optimization in the frequency domain, and thus a wider bandwidth in the region between 400 and 750 nm leads to a more accurate solution.…”
Section: Methodology a Coherence Scanning Interferometrymentioning
confidence: 99%
“…Figure 2 shows a good example of imaging system, the interferometric Linnik microscope [4,5]. It can be used as standard microscope when the reference path is blocked and it can be used as full field OCT system for deep imaging of biological tissue.…”
Section: Lc Devices In Biomedical Opticsmentioning
confidence: 99%